Extension’s Role in Rural Stress: An Evaluation of Extension Agents’ Perceptions of Rural Stress in Georgia - Madison C. Wilson; Whitney A. Stone; Jessica A. Holt; Kevan W. Lamm; Abigail S. Borron; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2019)
This was a qualitative, exploratory study examining the use of a word cloud activity with Extension agents to promote dialogue around the sensitive topic of farmer/rural stress to understand their community needs. With an increasing amount of health-related issues in rural America and abroad, particularly mental health and rural stress, the use of a word cloud activity helped identify individual regional needs through a visual thematic qualitative analysis. Through a constant comparative analysis, regional and state-wide themes were deduced to begin creating programming opportunities to address community needs in Georgia, the U.S., and the world. The identified themes indicated a need for support, resources and education in rural areas regarding farmer and rural stress.
Keywords: rural stress; farmer stress; mental health; Extension; qualitative